PIV measurements around 2D and 3D building models. (20th June 2008) - Brizzi, Laurent-E.; Poitras, Gerard J.; Gagnon, Yves
Particle image velocimetry (PIV) measurements for three Reynolds numbers were performed around two-dimensional and three dimensional model buildings that were placed inside an Eiffel type wind tunnel. For the 2D model, the height was half the length while for the 3D model the height equaled half the width and the length. Along with the velocity measurements, pressure measurements on the center plane of the models were also taken. Noticeable differences in the pressure coefficient distribution between the 2D and 3D models were observed. However, there are no significant Reynolds number effects in the range studied for both types of models.